Contraction mode and whey protein intake affect the synthesis rate of intramuscular connective tissue. Issue 1 (26th September 2016) - Holm, Lars; Rahbek, Stine Klejs; Farup, Jean; Vendelbo, Mikkel Holm; Vissing, Kristian
ABSTRACT: Introduction: In this study we investigated the impact of whey protein hydrolysate and maltodextrin (WPH) intake on intramuscular connective tissue (IMCT) protein fractional synthesis rate (FSR) after maximal shortening and lengthening contractions. Methods: Twenty young men were randomized to receive either WPH or maltodextrin [carbohydrate (CHO)] immediately after completion of unilateral shortening and lengthening knee extensions. Ring‐ 13 C6 ‐phenylalanine was infused, and muscle biopsies were obtained. IMCT protein FSR was measured at 1–5, as well as 1–3 and 3–5 hours after contractions and nutrient intake. Results: During the 1–3‐hour recovery, lengthening contractions resulted in a higher FSR than shortening contractions ( P  < 0.01), independent of supplementation type and, during the 3–5‐hour recovery, WPH had a higher FSR than CHO ( P  < 0.05), independent of prior contraction mode. Conclusions: The later appearance of a stimulating effect of WPH on the IMCT FSR after strenuous muscle contractions lends support to its ability to promote recovery of the muscle connective tissue matrix after exercise. Muscle Nerve 55 : 128–130, 2017